Transanal total mesorectal excision for rectal cancer: a multicentric cohort study. (8th November 2019) - Kang, Liang; Chen, Yuan-Guang; Zhang, Hao; Zhang, Hong-Yu; Lin, Guo-Le; Yang, Ying-Chi; Chen, Wen-Hao; Luo, Shuang-Ling; Chen, Ning; Tong, Wei-Dong; Shen, Zhan-Long; Xiong, De-Hai; et al.
Abstract: Background: Transanal total mesorectal excision (taTME) has recently emerged as a promising novel surgical procedure for rectal cancer. It is believed to hold the potential advantage of providing better access to mobilize the distal rectum and achieving better pathologic results. This study aimed to evaluate the feasibility of taTME for rectal cancer and summarize the preliminary experience in 10 Chinese hospitals. Methods: A total of 211 patients were enrolled in this study. Variables for evaluation of safety, feasibility, and oncologic outcomes were retrospectively collected and analysed. Results: The median distance between the tumor and the anal verge was 5.9 cm (range, 1.5–12 cm). The median operating time was 280 min (range, 70–600 min) and the median estimated intra-operative blood loss was 50 mL (range, 10–1, 500 mL). The overall rate of complication was 27.9%. Among the 211 patients, 175 (82.9%) had complete TME and 33 (15.6%) had near complete TME. The circumferential resection margin was negative in 97.7% of patients. The patients were followed for a median of 35 months (range, 2–86 months). There was 7.6% (16) mortality, 6.2% (13) had local recurrence, and 12.8% (27) had systemic recurrence. Kaplan–Meier survival analysis showed that 1-, 2-, and 3-year disease-free survival rates were 94.8%, 89.3%, and 80.2%, respectively, and 1-, 2-, and 3-year OS rates were 97.4%, 95.7%, and 92.9%, respectively. Conclusions: Although limited by its retrospective nature, taTME was safe and feasible in selected patients. Future work with rigorous data recording is warranted.